2019
DOI: 10.29271/jcpsp.2019.06.520
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Thin Layer Agar 7H11 for Direct Susceptibility Testing of Mycobacterium Tuberculosis Complex against Second Line Anti Tuberculosis Drugs on Smear Positive Specimens

Abstract: Objective: To evaluate performance of thin layer agar (TLA) 7H11 method for detection of ofloxacin (OFX) and kanamycin (KM) resistance in smear positive clinical specimens of patients with tuberculosis comparing the results with gold standard MGIT 960 system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
(4 reference statements)
2
2
0
Order By: Relevance
“…The overall median time until a CT DST result was 13 days, which is consistent with previous results by others [23,35]. Still, we found that a few of the CT plates were read very late, even 45 days after culturing (Fig 2 and 3) because our study protocol for indirect DST using the CT plates insisted of having 50 colonies in the control quadrant before reporting the results.…”
Section: Resultssupporting
confidence: 90%
“…The overall median time until a CT DST result was 13 days, which is consistent with previous results by others [23,35]. Still, we found that a few of the CT plates were read very late, even 45 days after culturing (Fig 2 and 3) because our study protocol for indirect DST using the CT plates insisted of having 50 colonies in the control quadrant before reporting the results.…”
Section: Resultssupporting
confidence: 90%
“…One could predict that this time could be slightly different and perhaps even shorter in routine settings, where the majority of cultured plates remain negative for 6 weeks and can quickly be examined 3 times weekly. The overall median time until a CT DST result was 13 days, which is consistent with previous results by others using the method either as an indirect or direct DST (Hussain et al, 2019;Toit et al, 2012). We found that a few of the CT plates were read very late, even 45 days after culturing (Figures 2 and 3).…”
Section: Discussionsupporting
confidence: 90%
“…The mean report time of TLA was very close to that of MGIT 960 from pulmonary specimens, within the range of from 9.6 to 12.5 days (Martin et al, 2009b;Satti et al, 2010), but we have not compared with MGIT 960 in pleural TB, simultaneously. Besides, TLA showed comparable results to MGIT 960 for the rapid detection of M.tb drug susceptibility (DST) of second line anti-TB agents (Minion et al, 2010;Ardizzoni et al, 2015;Hussain et al, 2019). However, whether TLA supplemented with Rpfs could be suitable and promote clinical drug resistance detection still needs further study.…”
Section: Discussionmentioning
confidence: 99%